THE ROLE OF SHADOWING TECHNIQUE IN DEVELOPING JAPANESE PRONUNCIATION COMPETENCE OF UZBEKISTAN-SPEAKING STUDENTS (American Journal of Interdisciplinary Research and Development, 2026)
This article analyzes the effectiveness of the shadowing technique in improving Japanese pronunciation among Uzbek-speaking students. It explains the nature of shadowing and its role in the simultaneous development of listening and speaking skills. The study highlights that this method is effective in mastering Japanese phonetics, intonation, and rhythm. The results indicate that shadowing is a practical and efficient tool for enhancing Japanese pronunciation skills.